Dinamika MBKM di Perguruan Tinggi Berbasis Pesantren: (Implementasi Hak Belajar Tiga Semester di Luar Program Studi) - Habibi, Wildan; Muzamil (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Pesantren-based universities still need assistance in implementing the MBKM curriculum. Limited human resources, financial facilities, and infrastructure are often found. This study aims to determine the dynamics of pesantren-based universities in implementing the curriculum, especially in the implementation of the right to study three semesters outside the study program. The research method used in this study is a qualitative approach with a data collection method through library research with primary data sources derived from articles that support the title study. The results of this study provide a general overview of pesantren-based universities that have been able to implement the program, including something that must be prepared in the implementation of MBKM related to the right to study three semesters outside the study program, collaborative PKM models between universities as joint bearers of MBKM-based activities. Opportunities to increase university cooperation with partners include student delegation as part of community service and teaching assistance as an effort to improve teaching skills and the introduction of new work environments that will be faced